AL-‘URF SOLUSI ISLAM DALAM MENGHADAPI KEMAJEMUKAN DARI MASA KE MASA - Hidayat, Asep Dadang; Mulyadi, Mulyadi; Gozaly, Ahmad Yusdi; Firmansyah, Ramdani (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This study aims to analyze and describe the rules of al-'Urf as an Islamic solution in dealing with pluralism in the present and the future. This qualitative research is included in research that uses descriptive analytical methods, with normative and anthropological legal research approaches. Data was collected using literature study techniques that prioritized the principle of usability. Furthermore, the data were analyzed using qualitative data analysis techniques through stages; studying, reducing, correcting, interpreting, and drawing conclusions that al'Urf has a long history which is used as evidence by the scholars in establishing law, relevant to the conditions of the era, time and place and does not contradict the Shari'ah. The results of this study are expected to be a reference for further research that is more comprehensive and more actual.